2011
DOI: 10.1038/nrendo.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 and energy balance: an integrated model of short-term and long-term control

Abstract: Glucagon-like peptide 1 (GLP-1), a peptide secreted from the intestine in response to nutrient ingestion, is perhaps best known for its effect on glucose-stimulated insulin secretion. GLP-1 is also secreted from neurons in the caudal brainstem, and it is well-established that, in rodents, central administration of GLP-1 potently reduces food intake. Over the past decade, GLP-1 has emerged not only as an essential component of the system that regulates blood glucose levels but also as a viable therapeutic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
163
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(171 citation statements)
references
References 124 publications
5
163
0
3
Order By: Relevance
“…The nodose ganglion also expresses receptors for GLP-1, PYY and CCK, supporting the established view that the afferent vagus nerve contributes to the anorexigenic actions of a number of endogenous hormones released locally within the intestinal epithelium (19,20). Acting on the intrinsic enteric plexus, Insl5, like several other metabolically relevant gut hormones, may contribute to the coordination of colon motility and secretion, ensuring the efficient mixing, fermentation and propulsion of ingesta.…”
Section: Discussionmentioning
confidence: 81%
“…The nodose ganglion also expresses receptors for GLP-1, PYY and CCK, supporting the established view that the afferent vagus nerve contributes to the anorexigenic actions of a number of endogenous hormones released locally within the intestinal epithelium (19,20). Acting on the intrinsic enteric plexus, Insl5, like several other metabolically relevant gut hormones, may contribute to the coordination of colon motility and secretion, ensuring the efficient mixing, fermentation and propulsion of ingesta.…”
Section: Discussionmentioning
confidence: 81%
“…To avoid hyperinsulinemia, secreted insulin would induce CEACAM1 phosphorylation to promote receptor-mediated insulin uptake (34) and hepatic insulin clearance (9, 10) to maintain normal insulin metabolism and action on glucose homeostasis. Given that GLP-1 prompts transition into the fasting state (35), this may also constitute a negative feedback mechanism to ultimately recover CEACAM2 levels and limit insulin secretion. Of note, CEACAM2 is expressed in the kidney but not liver (4,29).…”
Section: Discussionmentioning
confidence: 99%
“…Also in healthy and obese humans, the intravenous administration of GLP-1 reduces food intake in a dose dependent manner (Verdich et al, 2001). The results of studies on rodents have revealed that the effect of GLP-1 on the suppression of appetite is abolished by vagotomy which suggests that GLP-1 can act vagal and brainstem pathways (Abbott et al, 2005;Barrera et al, 2011).…”
Section: Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 95%